Evaluation of Character Education Management of Students of Senior High School State 2 Tondano - Lumapow, Harol R; Tuerah, Philotheus E A; Sumual, Shelty D.M.; Maringka, Riviva W; Wuwungan, Hansje T.; Rambitan, Maya C.; Rattu, Olviane I. (JR Education, 2024)
This study aimed to identify the management of student's character education at SMAN 2 Tondano. This study applied a qualitative approach. The data-collecting techniques were observation, interviews, and documentation. Data collected from that technique were analyzed by using data reduction, data presentation, and verification. The results of this study reveal that the implementation of character education in SMAN 2 Tondano has been integrated into school activity in three main forms: (1) combine with learning activities, (2) combine with extracurricular activities, (3) combine with cultivation and making people accustomed. The management of student character education in PUBLIC HIGH SCHOOL 2 Tondano students consists of (1) the planning of character education; (2) the organization of character education; (3) the implementation of character education; and (4) the supervision of character education.